Украина на пороге десятилетия: динамика застоя - Звиглянич, В. (Социология: теория, методы, маркетинг, 2001)
The author discusses reasons of the lingering poor situation in Ukraine on the threshold of its 10th Independence Anniversary. Useless character of efforts to organize ‘technological renaissance’ by application of West technologies and foreign historical experiences can be explained by ‘semantization’ of reality in particular. Therefore the stagnant structures of Ukrainian mentality (deeply rooted in social culture) need to be analyzed thoroughly.